Humic fractions as support for the classification of high-mountain Organossolos in the southeast of Brazil - Melania Merlo Ziviani; Luciele Hilda da Silva; João Pedro Comendouros Scott; Amanda Sales Alves; Luiz Alberto da Silva Rodrigues Pinto; Marcelo Souza Motta; Eduardo Carvalho da Silva Neto; Marcos Gervasio Pereira; Lúcia Helena Cunha dos Anjos (Revista Brasileira de Ciência do Solo)
ABSTRACT Brazilian Soil Classification System (SiBCS) adopts a hierarchical approach to classify soils using specific diagnostic attributes. Organossolos (Histosols) class is differentiated according to its genesis, especially because the parent material is organic, thus requiring diagnostic attributes that describe the unique properties of soil organic matter (SOM). This study aimed to propose the use of labile organic carbon and the C and N contents of humic fractions and their ratios for the family and series levels of the Brazilian Soil Classification System for Organossolos in high mountainous regions. Quantitative chemical fractionation of SOM was performed to obtain the humic fractions and determine the labile oxidizable carbon in 16 Organossolos profiles from Itatiaia National Park, RJ. Carbon and nitrogen contents of the humic acid, fulvic acid, and humin fractions were obtained, as well as the percentages of these fractions in relation to the total carbon and nitrogen in the soil. Carbon and nitrogen ratios were calculated for each fraction. Results showed little variation in the levels of labile organic carbon between the profiles but a large variation in total carbon and nitrogen levels, especially in the Organossolo Fólico Hêmico lítico profile. The ratios between the carbon and nitrogen of humic acids and fulvic acids (means of HAC/FAC = 1.61 and AHN/FACN = 1.05), carbon and nitrogen of the alkaline extract and humin (means of AEC/HUMC = 0.71 and AEN/HUMN = 0.38), carbon and nitrogen of the alkaline extract, and total carbon and total nitrogen (means of AEC/TC = 0.28 and AEN/TN = 0.19) were effective in determining the humification level of the profiles. This study proposes that the attributes evaluated, especially the ratio between the carbon of the alkaline extract of the humic substances (carbon of the fulvic acid fraction + carbon of the humic acid fraction) and the total soil carbon, as well as the ratio between the C and N of the humin fraction, should be used to define lower categorical levels of Organossolos. This new approach could facilitate the classification of these soils and contribute to a better understanding of the composition of Organossolos in Brazil.